A new application on fatty acid stability of fish fillets: Coating with probiotic bacteria-loaded polymer-based characterized nanofibers - Ceylan, Zafer; Meral, Raciye; Cavidoglu, Isa; Karakas, Canan Yagmur; Yilmaz, Mustafa Tahsin (WILEY, 2018)
The effect of coating with Lactobacillus rhamnosus-loaded poly[vinyl] alcohol and sodium alginate-based nanofibers (LR) and also poly(vinyl) alcohol and sodium alginate-based nanofiber (PS) on fatty acid stability of fish fillets was tested. LR and PS dope solutions were successfully electrospun. Scanning Electron Microscopy images of nanofibers, with 60.09 nm < diameter of nanofibers <522.1 nm, were defined to be smooth, cylindrical, and ultrafine. Thermal decomposition of LR and PS were determined as higher than 200 and 300 degrees C, respectively by Differential Scanning Calorimeter. Nanofibers could be used to keep the stability of Polyunsaturated fatty acids (PUFA)s such as eicosapentaenoic acid and docosahexaenoic acid in fish fillets. Besides PUFAs, the rapid changes in predominant Monounsaturated fatty acids (MUFA) value like oleic acid in fish fillets coated with LR and PS were successfully limited as compared to the uncoated samples. Polyene index and predominant saturated fatty acids values (C16:0, C18:0, and C14:0) of the samples coated with LR and PS were found to be more stabile. Furthermore, the sharply decrease in omega-3/omega-6 ratio of fish fillets was limited. Loading LR to PS provided higher atherogenic and thrombogenic index. The use of probiotic bacteria-loaded polymer-based characterized nanofibers has been determined to be a new application for the fatty acid stability of fish. Practical applications Applied tests revealed differences between the fatty acid profile of uncoated and coated samples. Enrichment of PS and NaAlG-based nanofibers with Lactobacillus rhamnosus provided better stable in terms of PUFA and MUFA in fish fillets.
Keywords: GILTHEAD SEA BREAM; FROZEN STORAGE; QUALITY; ENCAPSULATION; OIL; OMEGA-3-FATTY-ACIDS; SMOKING; DISEASE; PROFILE; FRESH; Biotechnology & Applied Microbiology; Food Science & Technology